Riscos nos processos de contratação e gestão contratual: o caso dos serviços terceirizados pela Universidade Federal do Pampa - Oliveira, Alexandre Borba de (2019)
This research focus is related to risks in contractual hiring and management processes in a Federal Higher Education Institution, restricted to continuous services that present full time working status. In this sense, the main objective is to explain how the risks that surround the hiring and management of outsourced services can compromise this process in the context of Universidade Federal do Pampa. It is defined as a qualitative research of applied nature and, concerning its objectives, as an investigative research. As for the choice of the study object, it is characterized as a case study. The hiring and management of outsourced services by Universidade Federal do Pampa was defined as the analysis unit to the research application. The data were collected through different sources of evidence, making use of documents, observation and semi-structured interviews with workers that kept/keep some direct link with the analyzed process. Content analysis and triangulation were applied as techniques for data study. One hundred and six risks were validated by the survey. The results show a series of risk cases that can compromise the reaching of the objectives in this study. A flawed planning, with inadequate quantitative estimates and incomplete reference terms, can have an impact on further phases of the process, causing impacts in the supplier selection and the contract management, resulting either in the termination of the hiring process, impeachments or the waste of budget/financial resources, all consequences of an unsuited planning. On the other hand, the selection of a supplier that does not present the qualifications needed, can cause impacts in the quality of services, causing an early interruption of the service. The wrongdoing in management and control of a contract, in its term, can cause, among others, illicit working, damage to the public purse and the possibility of shared responsibility of the administration. Through these results, it can be realized that the consequences from the risks that surround this processes are numerous, what demonstrates the need for preventive actions, in order to act to avoid these results in an appropriate and timely way. As a conclusion, it can be stated that the risks surrounding outsourced services hiring and management can result in legal, budget and financial implications, as well as operational and of integrity, and can compromise both public services and/or the fulfillment of the Institution mission.